Examining determinants of lifestyle interventions targeting persons with intellectual disabilities supported by healthcare organizations: Usability of the Measurement Instrument for Determinants of Innovations. Issue 4 (5th April 2019) - Steenbergen, Henderika A.; de Jong, Brenda I.; Fleuren, Margot A. H.; van der Schans, Cees P.; Waninge, Aly
Abstract: Background: Due to complex processes of implementation of innovations aimed at persons with intellectual disabilities in healthcare organizations, lifestyle interventions are not used as intended or not used at all. In order to provide insight into determinants influencing this implementation, this study aims to ascertain if the Measurement Instrument for Determinants of Innovations (MIDI) is useful for objectively evaluating implementation. Method: With semi‐structured interviews, data concerning determinants of implementation of lifestyle interventions were aggregated. These data were compared to the determinants questioned in the MIDI. Adaptations to the MIDI were made in consultation with the author of the MIDI. Results: All determinants of the MIDI, except for that concerning legislation and regulations, were represented in the interview data. Determinants not represented in the MIDI were the level of intellectual disabilities, suitability of materials and physical environment, multi‐levelness of interventions and several persons who could be involved in the intervention, such as direct support persons (DSPs), a therapist or family, and the communication between these involved persons. Conclusion: The present authors suggested making adjustments to existing questions of the MIDI in order to improve usability for deployment in organizations that provide care to persons with intellectual disabilities. The adjustments need to be tested with other interventions.